Chromosomal aberrations in spontaneously aborted products of conception from Ukraine - Tkach, I.R.; Huleyuk, N.L.; Zastavna, D.V.; Weise, A.; Liehr, T.; Ciszkowicz, E.; Tyrka, M. (Вiopolymers and Cell, 2017)
Aim. To investigate peculiarities of numerical chromosomal imbalances in spontaneous products of conception from Western region of Ukraine. Methods. GTG-banding, interphase mFISH with probe panels for chromosomes 13/21, 14/22, 15, 16, 17, 18, X and Y. Results. Cytogenetic and molecular cytogenetic studies on 419 spontaneously aborted fetuses were performed. An abnor-mal karyotype was detected in 35.80 %. Most often the detected aneuploidies were triploidy (27.3 %), monosomy X (22.7 %), and trisomy 16 (18.7 %), trisomy 21 (6.7 %), trisomy 15 (5.3 %) and trisomy 22 (5.3 %). Conclusion. Detection of chromosomal aneuploidies in samples from products of conception plays a key role to find out the reasons of reproductive failure in hu-mans. Our study showed the effectiveness of combining karyotyping and mFISH with the chosen probe set for increasing the detection rate in spontaneous abortions. Most likely while including cases with normal karyotype acc. to GTG-banding in the mFISH approach it would allow detec-tion of low level mosaics of aneuploidies as well. These studies were conducted for the first time in the western Ukrainian region. The obtained results were compared with the similar results from other countries.